2011
DOI: 10.1177/0954406211415320
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of the unsteady influence of an inlet guide vane

Abstract: The unsteady inlet guide vane (IGV)–impeller–diffuser interaction in a centrifugal compressor is investigated numerically and experimentally under different IGV prewhirl angles. The influence of IGV prewhirl angle on the flowfield and the unsteadiness of the impeller and diffuser are studied, and the mechanism of the unsteady IGV–impeller–diffuser interaction is explored. Results show that quite fair quantitative agreements are achieved between the predicted and measured flowfield. The IGV wake can decrease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…1 Many works have been carried out to investigate the influence of IGVs on energy performance, 2,3 internal flow field, 4,5 and unsteady interaction 6,7 for centrifugal compressors.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many works have been carried out to investigate the influence of IGVs on energy performance, 2,3 internal flow field, 4,5 and unsteady interaction 6,7 for centrifugal compressors.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and numerical approaches have been used to study compressor flow, with and without IGVs. Both can give valuable insight; however, both have their limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Early experimental and computational fluid dynamics (CFD) studies 4,6 showed that introducing preswirl increases the efficiency at lower mass flow rates and improves the surge limit. More recent studies have applied CFD simulations to investigate features such as performance, 7,8 unsteady interactions between the IGVs and the impellers, 9,10 pressure fluctuations at large IGV angles, 11 and the effect of IGV geometry. 1,12 A review of preswirl in from IGVs can be found in the work of Liu et al 13 Both experimental [14][15][16] and numerical 3,9,[17][18][19][20][21][22] approaches have been used to study compressor flow, with and without IGVs.…”
Section: Introductionmentioning
confidence: 99%
“…IGVs for centrifugal compressors have been thoroughly studied both experimentally and numerically. Zhou et al [1] investigated the unsteady IGVs-impeller-diffuser interaction in a centrifugal compressor, and found that the unsteadiness in the diffuser with negative IGVs angles was larger than that with positive prewhirl angles. Coppinger and Swain [2] demonstrated the test techniques and resulting analyses of the existing design of inlet guide vanes systems for industrial centrifugal compressor, and conducted some predictions of the performance of the improved IGVs system design.…”
Section: Introductionmentioning
confidence: 99%